Compressive Properties Of Green Rubber Foam From Reclaimed Rubber Glove - Noraiham, Mohamad; Mazliah, Mazlan; Jeefferie, Abd Razak; Nur Sharafina, Zainol; Amirul Asyraf, Mat Nasir; Hairul Effendy, Ab Maulod (Inderscience Enterprises Ltd., 2016)
Nowadays, green materials are of interest due to the changes of government policies in many countries towards sustainable product development. In this study, green rubber foam from reclaimed rubber glove at various sodium bicarbonate content (4, 6, 8, 10 and 12 phr) as blowing agent was prepared via melt compounding technique and expanded via two-step heat transfer foaming process. Compression testing and water absorption were performed and the results were then supported with morphological analysis. The crosslink densities determined using Flory-Rhener equation indicated the value had slightly decreased with increasing blowing agent. The 4 phr sodium bicarbonate generated the smallest cells and the highest relative density foam of 0.9. The foam exhibited the lowest water absorption rate of 1.7 × 10 g/min as well as the highest compressive strength of 105 kPa. Increasing blowing agent evidently increased the cell size and decrease the compressive strength of the foam.